Metody symulacji statycznej sieci gazowej = Simulation method static gas network - Gawron, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents methods for the simulation of static low-pressure gas network is characterized by rapid changes in pressure and velocity. Presented nonlinear algebraic mathematical models for calculating the relationship between pressure drop, the gas flow stream, geometric dimensions of pipes and pipeline gas properties.
Keywords: metody symulacji; sieci gazowe; simulation methods; gas networks